Highlighting the Place of Metastasis-Directed Therapy in Isolated Liver Metastases in Prostate Cancer: A Case Report - Yeo, Anne-Emmanuella; Hendrix, Aurore; Confente, Caterina; Christian, Nicolas; Mansvelt, Baudouin; Pairet, Géraldine; Seront, Emmanuel (Frontiers in Oncology, 2021)
Metastatic prostate cancer remains a challenge for clinicians. Metastases involve mainly the bone compartment and can manifest as oligometastatic disease. In this setting, the role of metastasis-directed therapies (MDT) including surgery and/or Stereotactic Body Radiotherapy are currently evaluated. Visceral metastases are less common and have very poor prognosis in mPC. Whether treating isolated visceral metastases such as liver metastases with MDT could increase the prognosis remains unknown. We report the management of a prostate cancer patient who progressed on androgen deprivation therapy with apparition of two liver metastases. We describe the feasibility of combining MDT with abiraterone acetate and prednisone in a patient with metastatic castration-resistant prostate cancer. MDT allowed interruption of abiraterone acetate, preventing cumulative toxicity of this agent.